Pemanfaatan Tumbuhan yang Digunakan dalam Pembuatan Alat Musik Tradisional Khas Suku Dayak di Kota Pontianak dan Sekitarnya - Elvi Rusmiyanto PW, Ferimonika Sari, Riza Linda, (Jurnal Protobiont, 2018)
The traditional musical instrument of Dayak tribes are the result of handicrafts that use the plants as raw materials of their manufacture processes. The purpose of this research was to idientify the types and parts of plants used in the production of traditional musical instruments of Dayak tribe in Pontianak city and surrounding areas. The research was conducted for five months from September 2016 to February 2017 at the Department of Tourism and Creative Economy of West Kalimantan Province to obtain data of craftsmens and artists of traditional musical instruments in Pontianakand surroundingareas. The research method used in this study was snowball technique with the number of respondents as much as 15 people while the data were collected using the semi-structured interview method with open-ended approaches. The result of the research showed that there were three types of traditional musical instrument of Dayak which are percussion, wind and stringed instrument. The dominant plant used by artisans wasjackfruit (Artocarpus heteropylus) and cempedak (Artocarpus integer) with 100% user frequency (FIC). The main part of the plant applied was the stem section.The application of other plant parts, such fruitand leaves were more commonly used as part of the traditional musical accessories especially kledi and sape’.